Phytochemical screening of secondary metabolite compounds in tammate leaf extract (Lannea coromandelica (HOUTT.) MERR.) from Pangkep Regency using various extraction methods - Iqbal, Muhammad; Jariah , Astri Ainun (Utan Kayu Publishing, 2025)
Lannea coromandelica (Houtt.) Merr., commonly known as Tammate, is a traditional medicinal plant with potential as a source of bioactive compounds. This study aimed to identify the secondary metabolite content in ethanol extracts of Tammate leaves using four different extraction methods: infusion, maceration, reflux, and Soxhlet extraction. The research methodology involved extracting the plant material with each technique, followed by phytochemical screening through color reactions and Thin Layer Chromatography (TLC). The results showed that the reflux method yielded the highest extract percentage at 18.77%, followed by maceration at 13.08%, Soxhlet at 5.14%, and infusion at 3.94%. Phytochemical screening indicated that reflux and maceration were more effective in extracting alkaloids, flavonoids, phenolics, tannins, saponins, and steroids, as confirmed by both color reactions and TLC. In contrast, the infusion method showed the least effectiveness. These findings emphasize the importance of selecting appropriate extraction methods to optimize the isolation of bioactive compounds. The implications of this study support the development of efficient extraction techniques in the natural-based pharmaceutical industry and contribute to the utilization of local Indonesian medicinal plants. Further research is recommended to conduct quantitative analyses of the main compounds and to evaluate the pharmacological activities of the extracts.